Natural Tourism planning and sustainable tourism in Libya The case of the Derna region - Aziza, Salah Abu; Boudjemaa, Khalfallah (Technium Business and Management, 2024)
The Derna region experienced a violent hurricane in 2023 that destroyed much of the infrastructure and residential neighborhoods. The area requires extensive reconstruction that takes into account the natural and touristic qualities of the place, beyond the obvious shortcomings in tourism planning processes. It is time to pay attention to this important sector, by adopting urban plans that are updated and modified according to circumstances in order to create a sustainable tourism project. The Derna region in eastern Libya is one of the cities that, if it benefits from tourism urban programs adopted within a national strategy for sustainable tourism development, will constitute a tourism pole not only in Libya but also at the regional level. The area is coastal, characterized by stunning natural landscapes with the presence of the sea, valley and plateaus. It is also located within a rich tourism field that provides the practice of various types that attract tourists at different levels, capabilities and ambitions, and establishes true sustainable tourism. However, the effectiveness of the tourism sector in the region and in all cities of the Libyan country is still modest in its practice compared to the opportunities and capabilities available. It also does not have sustainability requirements, as it does not have an effective tourism plan. This requires a redoubled effort to overcome various challenges and create a sustainable future tourism project.